2015
DOI: 10.1109/tap.2015.2436442
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of a Plane Wave by a Homogeneous Anisotropic Elliptic Cylinder

Abstract: A formal series solution to the problem of scattering of a normally incident plane wave from an infinite homogeneous anisotropic elliptic cylinder is presented. The formulation of the problem is accomplished by assuming that the permittivity and the permeability tensors of the anisotropic material referred to the elliptic cylindrical coordinate axes are mainly biaxial and diagonal, and expanding each field associated with the problem in terms of a series of suitable Mathieu functions and expansion coefficients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…The even and odd angular Mathieu functions are written in terms of Fourier series as (19) (20) Substituting equations (16) to (20) into equation (14), and can finally be written in terms of the slot field as…”
Section: Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The even and odd angular Mathieu functions are written in terms of Fourier series as (19) (20) Substituting equations (16) to (20) into equation (14), and can finally be written in terms of the slot field as…”
Section: Formulationmentioning
confidence: 99%
“…The extension of the solution to the radiation by N slotted elliptical antenna coated with lossy dielectric material was investigated by showing the effect of lossy dielectrics material on its characteristics [7]. Solutions to materials having lossy or lossless metamaterials as well as chiral material gained considerable attention of several researchers [8][9][10], while solutions having anisotropic materials have been presented by [11][12][13][14][15][16]. It was shown that the metamaterial coating enhances the gain of the antenna while the anisotropic and chiral materials produce co and cross polarized fields.…”
Section: Introductionmentioning
confidence: 99%
“…The above tensors are generally expressed relative to either a Cartesian coordinate system designated by = , = or a circular cylindrical coordinate system designated by = , = . Using (A3)-(A14) in [19], it can be shown that the elements of (3) in a Cartesian or a…”
Section: Transmitted Fieldmentioning
confidence: 99%
“…In [17], 2-D scattering of a transverse electrically polarized normally incident plane electromagnetic wave from a weakly lossy homogeneous gyrotropic elliptic cylinder has been examined, by expressing the electromagnetic fields inside the cylinder using integrals involving Mathieu functions and Fourier series developed in [18], and then employing a first-order Taylor series expansion to calculate Mathieu functions having complex arguments. A formal series solution to the problem of scattering from an infinite homogeneous anisotropic elliptic cylinder excited by a normally incident transverse magnetically polarized plane wave was obtained recently in [19], but when the permittivity and permeability tensors of the anisotropic material referred to the elliptic coordinate axes are biaxial and diagonal. An exact series solution is reported here for the first time, to the problem of scattering of a plane wave by an infinitely long homogeneous G-type elliptic cylinder, for transverse electric (TE) polarization of the incident wave, when the plane wave is incident normal to its axis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation